Gliomatosis Cerebri in a Dog - Sant’Ana, Fabiano J. F. de; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2011)
A 6-year-old, female, mixed-breed dog was presented for necropsy with history of prostration and incoordination followed by circling to the right and seizures. There were no gross findings in the brain. Histologically, there were numerous neoplastic glial cells throughout the thalamus, midbrain, pons and medulla oblongata. Moderate multifocal lymphoplasmacytic perivascular cuffings were also present in the same areas. In addition, severe multifocal proliferation of glial cells was observed in the leptomeninge and white matter of the cerebellum. The neoplastic cells observed in the brain stem were negative for GFAP, while in the cerebellum the neoplastic glial cells were strongly labeled with GFAP and vimentin. Based on the histopathological findings and on the immunohistochemical results, a diagnosis of gliomatosis cerebri was made.